ESTIMATING THE PROBABILITY OF MISCLASSIFICATIONS IN TWO-GROUPS DISCRIMINANT ANALYSIS - I W. MANGKU (MILANG Journal of Mathematics and Its Applications, 2004)
This paper is a survey study on estimation of the pro- bability of misclassiﬁcations in two-groups discriminant analysis using the linear discriminant function as the classiﬁcation rule. Here we consider two groups of estimators, namely parametric esti- mators and empirical estimators. The results of some comparative studies on the performances of the considered estimators are also discussed.